NK cell exhaustion in the tumor microenvironment - Jia, Hao; Yang, Hongmei; Xiong, Huaxing; Luo, Kathy Qian (Frontiers in Immunology, 2023)
Natural killer (NK) cells kill mutant cells through death receptors and cytotoxic granules, playing an essential role in controlling cancer progression. However, in the tumor microenvironment (TME), NK cells frequently exhibit an exhausted status, which impairs their immunosurveillance function and contributes to tumor immune evasion. Emerging studies are ongoing to reveal the properties and mechanisms of NK cell exhaustion in the TME. In this review, we will briefly introduce the maturation, localization, homeostasis, and cytotoxicity of NK cells. We will then summarize the current understanding of the main mechanisms underlying NK cell exhaustion in the TME in four aspects: dysregulation of inhibitory and activating signaling, tumor cell-derived factors, immunosuppressive cells, and metabolism and exhaustion. We will also discuss the therapeutic approaches currently being developed to reverse NK cell exhaustion and enhance NK cell cytotoxicity in the TME.